Medical Computer Vision. Recognition Techniques and Applications in Medical Imaging International MICCAI Workshop, MCV 2010, Beijing, China, September 20, 2010, Revised Selected Papers - Menze, Bjoern; Langs, Georg; Tu, Zhuowen; Criminisi, Antonio (Lecture Notes in Computer Science, 2011)
This book constitutes the thoroughly refereed post-workshop proceedings of the International Workshop on Medical Computer Vision, MCV 2010, held in Beijing, China, in September 2010 as a satellite event of the 13th International Conference on Medical Image Computing and Computer Assisted Intervention, MICCAI 2010. The 10 revised full papers and 11 revised poster papers presented were carefully reviewed and selected from 38 initial submissions. The papers explore the use of modern image recognition technology in tasks such as semantic anatomy parsing, automatic segmentation and quantification, anomaly detection and categorization, data harvesting, semantic navigation and visualization, data organization and clustering, and general-purpose automatic understanding of medical images.